Development and validation of Midwifery Vocational Perception Scale - Zümrüt Bilgin; Yeliz Doğan Merih (Mashhad University of Medical Sciences, 2021)
Background & aim: Vocation perception of midwives is important in terms of their sense and level of professionalism. The  purpose of this study was to develop and validate Midwifery Vocational Perception Scale.Methods: This validation study was carried out at five public hospitals located in Istanbul, Turkey from October 1st to December 30th, 2019. In the first stage, 68 items draft form was prepared. After receiving the opinion of seven experts, the face validity of the scale was tested with 20 midwives. In the second stage, the 5-point 52-item Likert scale was administered to 282 midwives. However, since the outliers were deleted before the factor analysis, the analysis was performed for only the data of 232 people. Factor and confirmatory analyses and the Cronbach's alpha coefficient were used to analyze the scale validity and reliability.Results: According to the exploratory factor analysis, the scale consisted of 16 items and three factors that explained 53.085% of the the scale variance.  Confirmatory factor analysis fit index results were found as CMIN=175,427, DF=97, p<0.001, CMIN/DF=1.809, RMSEA=0.059, CFI=0.933, GFI= 0.916. The Cronbach's alpha value of scale was determined to be 0.865. The lowest anyone scored was 16, the highest was 80, while  the mean score was 87.71 ±7.46 (min: 67, max: 95).Conclusion: A high score indicates positive vocational perception and occupational opinions in midwifery, while a low score indicates negative vocational perception and occupational opinions. The Midwifery vocational Perception Scale was prepared in Turkish and a validity study in other cultures is recommended.